Graphene Embedded Modulator with Extremely Small Footprint and High Modulation Efficiency. (28th May 2014) - Hao, Ran; Jin, Jia-Min
Abstract : By embedding graphene sheet in the silicon waveguide, the overall effective mode index displays unexpected symmetry and the electrorefraction effect has been significantly enhanced near the epsilon-near-zero point. An eight-layer graphene embedded Mach-Zehnder Modulator has been theoretically demonstrated with the advantage of ultracompact footprint (4 × 2  μ m 2 ), high modulation efficiency (1.316 V · μ m), ultrafast modulation speed, and large extinction ratio. Our results may promote various on-chip active components, boosting the utilization of graphene in optical applications.